Domestic partnership and inheritence rights - Castillo Freyre, Mario (2013)
In this article, the author comments -from constitutional and civil perspectives- the scope of Law Nº 30007, whose purpose is to recognize inheritance rights between domestic partners. Similarly, the paper analyzes the practical problems faced when applying such Law. Among them, the author does not believe that the mere fact of concubines concurring is sufficient to determine inheritance rights. Consequently, in case of multiple domestic partnerships, and in case of several cohabitants having hereditary rights, the courts should make prevail the most stable domestic partnership and the one that most resembles a marital union.